2009
DOI: 10.1097/icu.0b013e32832f8002
|View full text |Cite
|
Sign up to set email alerts
|

Childhood macular dystrophies

Abstract: Molecular diagnosis and improvements in retinal imaging have greatly improved the accuracy of diagnosis in paediatric macular disease and allowed better genetic counselling and information about prognosis to be given to children and their families. Advances in basic understanding of disease mechanism will lead to the development of clinical trials of novel therapies in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Devastating and untreatable vision loss of children and young adults are caused by certain gene mutations affecting the photoreceptors of the fovea and the surrounding region called the macula [46]. In addition, foveas in the elderly are commonly affected with age-related macular degeneration (AMD), a multifactorial disease with a strong genetic component [47].…”
Section: Resultsmentioning
confidence: 99%
“…Devastating and untreatable vision loss of children and young adults are caused by certain gene mutations affecting the photoreceptors of the fovea and the surrounding region called the macula [46]. In addition, foveas in the elderly are commonly affected with age-related macular degeneration (AMD), a multifactorial disease with a strong genetic component [47].…”
Section: Resultsmentioning
confidence: 99%
“…The inherited macular dystrophies are a clinically and genetically heterogeneous group of disorders in which there are structural and functional abnormalities of the central retina [1], [2]. These disorders usually occur in isolation, but they may be associated with a variety of systemic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Postnatal degeneration of photoreceptors underlies the most common causes of irreversible blindness. Rod-cone photoreceptor dystrophy is a group of congenital retinal degenerative disorders characterized by postnatal onset of progressive photoreceptor cell loss 1 2 , leading to severe visual impairment and deterioration. Molecular genetic studies have revealed the underlying causes in only ∼50% of these patients.…”
mentioning
confidence: 99%